Oxidant and antioxidant levels in preterm newborns with idiopathic hyperbilirubinaemia - Turgut, M; Basaran, O; Çekmen, M; Karatas, F; Kurt, A; Aygün, AD (Wiley, 2004)
Objectives: Newborns, particulary preterm infants, have limited antioxidant protective capacity. The organism's defence system against reactive oxygen species including vitamins A, E and C, trace element selenium (Se) and enzymes, such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) are essential components of the antioxidant system against the oxidative injury to the cellular membranes of erythrocytes. In this study, our aim was to compare the oxidant nitric oxide (total plasma nitrite level as an indicator of nitric oxide (NO)), antioxidant vitamins and selenium and erythrocyte antioxidant enzymes in premature babies with hyperbilirubinaemia with healthy preterms. Methods: Twenty preterm infants with newborn jaundice were included in the study group, while 15 preterm infants without jaundice were enrolled in the control group. We evaluated the mean plasma levels of, respectively, the total nitrite as an indicator of NO, bilirubin, vitamins A, E, C and selenium, and the activity of erythrocyte antioxidant enzymes such as CAT, SOD and GSH-Px of preterm infants with idiopathic hyperbilirubinaemia and compared to those of the control group. Results: The mean plasma total nitrite and total serum bilirubin levels and blood reticulocyte counts of the study group were found to be significantly higher than those of the control group (P < 0.001, P < 0.001 and P < 0.05, respectively). Furthermore, the activity of erythrocyte antioxidant enzymes (all P < 0.001) and the mean plasma levels of the antioxidant vitamins A, E, and C (P < 0.05, P < 0.05 and P < 0.001, respectively) and selenium (P < 0.001) of the study group were all found to be significantly lower than those of the control group. Conclusion: We hypothesize that low antioxidants in pretem babies may predispose them to increased oxidative stress, and cause hyperbilirubinaemia.
Keywords: antioxidants; hyperbilirubinaemia; nitric oxide; nitrite; preterm; selenium; vitamins